Optical modulation at around 1550 nm in an InGaAlAs optical waveguide containing an InGaAs/AlAs resonant tunneling diode - Figueiredo, J. M. L. (2012)
We report electroabsorption modulation of light at around 1550 nm in a unipolar InGaAlAs optical waveguide containing an InGaAs/AlAs double-barrier resonant tunneling diode ~RTD!. The RTD peak-to-valley transition increases the electric ﬁeld across the waveguide, which shifts the core material absorption band edge to longer wavelengths via the Franz–Keldysh effect, thus changing the light-guiding characteristics of the waveguide. Low-frequency characterization of a device shows modulation up to 28 dB at 1565 nm. When dc biased close to the negative differential conductance region, the RTD optical waveguide behaves as an electroabsorption modulator integrated with a wide bandwidth electrical ampliﬁer, offering a potential advantage over conventional pn modulators.